The origin of island populations of the African malaria mosquito, Anopheles coluzzii - Campos, Melina (2021)
Funding Information: This work was supported by grants from the UC Irvine Malaria Initiative Program, Open Philanthropy and NIH R56 grant (R56AI130277). We thank the National Malaria Control Program personnel from São Tomé and Príncipe and, Ministry of Health in São Tomé and Príncipe who facilitated our field collections in São Tomé. We thank the Centre International de Recherches Médicales de Franceville (Franceville, Gabon) for the collections in Gabon. Publisher Copyright: © 2021, The Author(s).